Public-Private Partnerships in driving Sustainable Agricultural Growth for Addressing Poverty and Food Insecurity in Nigeria - Amuda, Yusuff Jelili; Parveen, Rehana (Journal of Ecohumanism, 2024)
Poverty and food insecurity have become a concern in various parts of the world including Nigeria which are regarded as impediments for achieving sustainable development goals (SDGs). Overwhelming studies have explored the roles and contributions of public-private partnerships (PPP) in driving various aspects of the economy in general and gross domestic product (GDP) in particular. However, less focus of attention is given to public-private partnerships (PPP) in fostering the sustainable agricultural growth in Nigeria in order to addressing poverty and food insecurity in Nigeria. Content and critical analysis is used in this study as a methodological approach. Secondary data were used which were sourced through academic databases such as journals from google scholar. The result demonstrated that the current hike in the price of commodities in the country contribute to the proliferation of poverty among the households and the challenges of kidnapping and banditry immensely contribute to the challenge of food security in the country. The challenge of funds identified among the farmers contribute immensely to high level of poverty and prevalence of food insecurity in the country. It is therefore suggested that the government should encourage provision of funds through an effective collaboration of public-private partnerships (PPP) in driving sustainable agriculture growth in the country. In so doing, it would strengthen the income of households through farming and sustainable agricultural productivity for poverty alleviation and food security will be achieved.